Environmental management archetypes: model proposition from Rio Grande do Sul companies - Dalmoro, Marlon; Cyrne, Carlos Candido da Silva (Revista de Administração da UFSM, 2017)
This paper aims to develop a descriptive model of basic behaviors of environmental management from the analysis of how local companies have managed the environmental issues. For this, we initially built a theoretical body on environmental management identifying possible types of environmental management behaviors. For empirical plan development, our data source was the Annual Review of Environmental Management Practices, published by Análises Editorial, describing environmental management practices of 49 companies, of 28 different branches of economy, located in Rio Grande do Sul - Brazil. Results show that environmental management behaviors have been guided by the involvement of top management in environmental management and establishment of goals and plans for organizational environmental development. Based on these results, we propose a model with five different archetypes that seek to express behaviors adopted in the environmental management by companies from Rio Grande do Sul - Brazil.